RCPA STANDARDS FOR CLINICAL DATABASES OF GENETIC VARIANTS. (February 2015) - Bennetts, Bruce; Caramins, Melody; Hsu, Arthur; Lau, Chiyan; Mead, R. Scott; Meldrum, Cliff; Suthers, Graeme; Taylor, Graham; Tyrrell, Vanessa
Abstract : It is routine practice to compare sequence variations identified during clinical genetic testing with variants recorded in a wide range of databases and scientific literature. Many sequence variation databases have been established globally, however few meet the standards required for reliable use in clinical diagnostics. The Royal College of Pathologists of Australasia in collaboration with the Human Genetics Society of Australasia, and Human Variome Project has developed standards for DNA sequence variation databases intended for use in the clinical environment. The fundamental principle of the document is to provide a standard for oversight of clinical databases of genetic variants to ensure they are developed, curated, and maintained as safe, secure, accurate repositories of genomic data. They are intended to complement and align with existing laboratory standards, accreditation requirements, global initiatives and best practice guidelines, act as a guide to identify a quality database, develop new, improve existing, and set minimum requirements for clinical purposes within existing legislation nationally and globally. The standards framework conforms to NPAAC reference materials and addresses clinical database requirements in a systematic order with clearly defined, concise criteria considering challenges related to: database purpose, governance, establishment, protection, privacy, security, content, functionality, access, sharing, and curation.